2001
DOI: 10.1046/j.1365-2249.2001.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 gene transcripts in rheumatoid arthritis

Abstract: SUMMARYSusceptibility to rheumatoid arthritis (RA) is associated with defined HLA-DRB1 alleles. However the molecular basis of this association is not known. Peculiarities in the expression of disease-linked DRB1 alleles could be involved since in healthy controls HLA-DRB1 gene expression varies according to the alleles in B cells. Peripheral blood B cells of healthy controls and RA patients were examined for their level of allelic DRB1 transcripts using a competitive PCR approach. Levels of DRB1 transcripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…In this regard, it is important to note that this cohort of Chinese RA patients is preferentially associated with DRB1*0405 (43% patients), which is different from two other genotypes of DR4 (DRB1*0404 and DRB1*0401) closely linked with Caucasian RA patients. [3][4][5] Our study further revealed a trend toward correlation between the overexpression of BV16 but not BV14 in synovial T cells and DRB1*0405 in RA patients. However, the sample size was too small to allow meaningful statistical analysis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In this regard, it is important to note that this cohort of Chinese RA patients is preferentially associated with DRB1*0405 (43% patients), which is different from two other genotypes of DR4 (DRB1*0404 and DRB1*0401) closely linked with Caucasian RA patients. [3][4][5] Our study further revealed a trend toward correlation between the overexpression of BV16 but not BV14 in synovial T cells and DRB1*0405 in RA patients. However, the sample size was too small to allow meaningful statistical analysis.…”
Section: Discussionmentioning
confidence: 66%
“…In this cohort of Chinese RA patients, genotype DRB1*0405 represented the most dominant DR4 (16/37, 43%) compared to two other DR4 genotypes (DRB1*0401 (8%) and DRB1*0404 (3%)) that are typically associated with Caucasian RA patients. [3][4][5] In addition, DRB1*09012 (35%) and three DQB1 genotypes (0301, 0303 and 0401) were also frequently expressed in this cohort of RA patients (30-41%).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…81 There was, however, consistency seen between the in vitro reporter assays and assayed transcript levels in vivo with higher transcript abundance in resting peripheral B cells with the DR52 haplogroup (HLA-DRB1*03, *11, *13 and *14) as compared with the DR53 haplogroup (HLA-DRB1*04, *01 and *09). 79,80 The evidence from H-2 genes in the mouse supports haplotype-specific differential gene expression with striking evidence of specific promoter variants, for example, in the X2 box, resulting in allele-specific expression. Remarkably, this was specific to particular cell types, in macrophages, for example, altering the subsequent T-cell cytokine response.…”
Section: Mhc Haplotypes Sequence Variation and Class II Regulationmentioning
confidence: 99%
“…[71][72][73] Polymorphism altered gene expression in resting cells [71][72][73][74] but interestingly after cytokine activation, variation in the Y rather than the X1 box was significant. 75 For HLA-DRB1, low and high expressing alleles were defined based on reporter gene analysis using specific promoter constructs 72,73,[76][77][78] and assays of transcript abundance in immortalized B-cell lines or B cells from peripheral blood, 77,79,80 although analysis of nascent and steady-state messenger RNA using the latter did also indicate a role for post-transcriptional mechanisms in some of the differences observed. 81 There was, however, consistency seen between the in vitro reporter assays and assayed transcript levels in vivo with higher transcript abundance in resting peripheral B cells with the DR52 haplogroup (HLA-DRB1*03, *11, *13 and *14) as compared with the DR53 haplogroup (HLA-DRB1*04, *01 and *09).…”
Section: Mhc Haplotypes Sequence Variation and Class II Regulationmentioning
confidence: 99%